2020
DOI: 10.3390/microorganisms8020167
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ambiguous Status of Coagulase-Negative Staphylococci in the Biosafety of Fermented Meats: The Case of Antibacterial Activity Versus Biogenic Amine Formation

Abstract: A total of 332 staphylococcal strains, mainly isolated from meat, were screened for antibacterial activity. Eighteen strains exhibited antibacterial activity towards species within the same genus. These antibacterial strains were further screened against Clostridium botulinum, to assess their potential as anticlostridial starter cultures for the development of fermented meat products without added nitrate or nitrite. Only Staphylococcus sciuri IMDO-S72 had the ability to inhibit all clostridial strains tested,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 96 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Putrescine (PUT) and cadaverine (CAD) were not detected in all samples at the initial stage of fermentation, but they sharply increased in NS samples after eight weeks of fermentation, much higher than those in groups SBM and WBX. It has been reported that PUT and CAD are linked with the presence of enterobacteria (Van der Veken et al ., 2020), Aeromonas and Pseudomonas (Liu et al ., 2018). The concentration of tyramine (TYR), spermine (SPM) and spermidine (SPD) in NS samples increased during the fermentation, while the content of the three biogenic amines fluctuated in the samples of SBM and WBX and was much lower than those in NS samples.…”
Section: Resultsmentioning
confidence: 99%
“…Putrescine (PUT) and cadaverine (CAD) were not detected in all samples at the initial stage of fermentation, but they sharply increased in NS samples after eight weeks of fermentation, much higher than those in groups SBM and WBX. It has been reported that PUT and CAD are linked with the presence of enterobacteria (Van der Veken et al ., 2020), Aeromonas and Pseudomonas (Liu et al ., 2018). The concentration of tyramine (TYR), spermine (SPM) and spermidine (SPD) in NS samples increased during the fermentation, while the content of the three biogenic amines fluctuated in the samples of SBM and WBX and was much lower than those in NS samples.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of agmatine, cadaverine, histamine, 2-phenylethylamine, putrescine, spermidine, spermine, tryptamine, and tyramine were quantified with external calibration, in triplicate, by UPLC-MS/MS, using an Acquity system equipped with an HSS T3 column (Waters), as described previously ( Van der Veken et al, 2020 ). Samples were prepared by addition of 300 μL of acetonitrile (Merck) with 0.2% heptafluorobutyric acid (Sigma-Aldrich) to 300 μL of aqueous extracts, followed by microcentrifugation at 18,000 × g for 15 min, and filtering with a 0.2-μm LG H-PTFE filter (Millex; Merck) before injection (5 μL) into the column.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, M. sciuri (strain IMDO-S72) was associated with the production of the thiopeptide micrococcin P1. This strain was originally isolated from fermented meat and attracted interest because of its potent antibacterial activity towards Clostridium botulinum and other foodborne pathogens in previous research (43). The present study aimed at identifying the compound responsible for this antibacterial activity as well as the characterization of the BGC necessary for its production.…”
Section: Introductionmentioning
confidence: 99%